EFFECT OF CONSERVATION AGRICULTURE ON WATER CONSUMPTION OF BARLEY AND MUNGBEAN IN GYPSIFEROUS DESERT SOIL - Mohammed A. M. AL-Rawi; Mohammed H. Bahia (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The field experiment was carried out during 2021-2022 in the Lower Al-Jazeera region at Anbar - Iraq. The study aimed to find the effect of conservation tillage and coverage practice on water use and consumption of crops in gypsum desert soil in two seasons using two cover crops (Barley and Mung bean). The experiment was carried out on abandoned land, so the covering (straw) was added when planting barley, and then the barley residual was kept when planting Mung bean. Non-inversion tillage was used by the digger plow. Randomly four treatments, tillage covering T.C, tillage no-covering T.NC, no-tillage covering NT.C, and no-tillage no-covering NT.NC was distributed on 12 experimental units by using RCBD design. Irrigation under sprinkler system. Results showed a significant effect of the T treatments on water consumption (ETa) in the winter season in the Mid-stage, with a difference of 16% from the NT, and for the C treatments in the Div-tage, with a difference of 37.6% from the NC. In the Inti-stage of the summer season, the T and C treatments used significantly less water by 18% and 13% compared to the NT and NC treatments, respectively. While in consumption ETa, showed a significant difference for T treatments by 6% less than NT in the Inti-stage and for C treatments in the Dev-stage by 13 % less than NC. The interference treatments T.C least and NT.NC higher used and consumed.